A How-to Guide for Open-Science Practices in Special Education Research. (August 2022) - Cook, Bryan G.; Fleming, Jesse I.; Hart, Sara A.; Lane, Kathleen Lynne; Therrien, William J.; van Dijk, Wilhelmina; Wilson, Sarah Emily
Open-science reforms, which aim to increase credibility and access of research, have the potential to benefit the research base in special education, as well as practice and policy informed by that research base. Awareness of open science is increasing among special education researchers. However, relatively few researchers in the field have experience using multiple open-science practices, and few practical guidelines or resources have been tailored to special education researchers to support their exploration and adoption of open science. In this article, we described and provided guidelines and resources for applying five core open-science practices—preregistration, registered reports, data sharing, materials sharing, and open-access publishing—in special education research.